EFEKTIVITAS AKUN INSTAGRAM DITJEN DIKTI @DITJEN.DIKTI TERHADAP PEMENUHAN KEBUTUHAN INFORMASI PENDIDIKAN TINGGI (Survei Pada Pengikut Aktif Akun Instagram @ditjen.dikti) - Mutiara Sabrina, (2023)
The emergence of new media alongside the advancement of information technology has had a significant impact on society. In the field of communication, one of them is the use of social media such as Instagram. Not only for personal use, but now Instagram accounts are also used by various organizations and government agencies. One government agency that utilizes social media for information dissemination is the Directorate General of Higher Education (Ditjen Dikti). This thesis will discuss whether Ditjen Dikti, through its Instagram account, has effectively provided higher education information to its followers. The research conducted is quantitative in nature, based on the data, and explanatory in the form of a survey based on its methodology. The results of this study indicate that the Instagram account @ditjen.dikti, which publishes higher education information, meets the followers' needs in terms of passive attention, active search, passive search, and continued search, as seen from the coefficient of determination test, which shows an R-Square value of 0.824. This means that the effectiveness of the Ditjen Dikti Instagram account in fulfilling information needs is 82.4%, while the remaining 17.6% is identified as not meeting their information needs despite the existence of the Instagram account. Keywords: Ditjen Dikti, Effectiveness, Information Needs, Instagram.